Ileocecal mucinous carcinoma misdiagnosed as incarcerated hernia: A case report - Ji Xiang; Wang Meng; Zhao Aihong; Ding Jian; Zhang Yunjie (Open Life Sciences)
Mucinous carcinoma is a rare clinical disease. Although well described in the literature, a mucinous carcinoma diagnosis is often difficult due to its atypical clinical presentation. We report a female patient with a right inguinal mass and ileocecal myxo carcinoma who was misdiagnosed as having a right incarcerated inguinal hernia invading the peritoneum incarcerated inguinal hernia and ileocecal myxo carcinoma. Intraoperative exploration of the mucous material occupying the patient’s right lower abdominal cavity and exclusion of right inguinal incarcerated hernia revealed the misdiagnosis. The first clinical manifestations of ileocecal mucinous carcinoma are often not readily apparent and may be misdiagnosed as an incarcerated inguinal hernia. When a color ultrasonography suggests an incarcerated inguinal hernia, an abdominal CT should be considered, and an enhanced CT should be performed as needed to observe the abdominal cavity. Ileocecal mucinous carcinoma should also be distinguished from other diseases with similar clinical manifestations. The patient had received conservative treatment for acute appendicitis, and it is recommended to conduct a B-ultrasound, CT, and other reviews after surgery. Clinicians should be aware of missed surgical opportunities following appendicitis caused by mucinous adenoma.